Guidelines and recommendations for cross-linguistic aphasia assessment: a review of 10 years of comprehensive aphasia test adaptations - Martinez-Ferreiro, Silvia; Arslan, Seçkin; Fyndanis, Valantis; Howard, David; Kraljevic, Jelena Kuvac; Škorić, Ana Matić; Ibarrola, Amaia Munarriz; Norvik, Monica I.; Peñaloza, Claudia; Pourquie, Marie; Simonsen, Hanne Gram; Swinburn, Kate; et al. (My University, 2024)
Background: Standardised aphasia assessment tools may not always be available in a variety of languages, posing challenges for speech and language therapists to adequately assess and diagnose aphasia in speakers of those languages. In 2013, Working Group 2 (WG2) Aphasia Assessment & Outcomes, part of the Collaboration of Aphasia Trialists network, was formed with the purpose of developing reliable and valid aphasia assessment tools and their cross-linguistic adaptations. Over the past decade, WG2 has undertaken important adaptation projects, including the cross-linguistic adaptation of the Comprehensive Aphasia Test (CAT; Swinburn et al., 2004). Aims: This review aims to achieve three objectives: (a) describe the adaptation procedure of the CAT within WG2, (b) summarise common guidelines and recommendations for future adaptations, and (c) provide concrete solutions for specific cross-linguistic and cross-cultural challenges encountered during the adaptation and validation procedures of the CAT. Methods: Between 2013 and 2023, WG2 employed a committee approach and fully adapted the CAT into Catalan, Croatian, Dutch, French, Hungarian, Norwegian, Spanish, and Turkish. Further adaptations are in progress for Arabic (Moroccan), Basque, Cantonese Chinese, German, Greek, Icelandic, Lithuanian, Serbian, Slovenian and Swedish. The review comprehensively addresses the linguistic/cultural adaptation and validation procedure for the three components of the battery: the Cognitive screening, the Language battery and the Aphasia Impact Questionnaire. Critical outcomes and some best practice recommendations from psychometric norming and piloting are also discussed. Outcomes and results: This review builds upon prior work (Fyndanis et al., 2017) and serves as a practical guide for researchers and clinicians undertaking cross-linguistic adaptations of the CAT, with specific conclusions and recommendations drawn from WG2’s adaptations in 19 languages with diverse typological properties. Building on the work exemplified in this paper, future initiatives can direct their efforts towards adapting the CAT for PWA from different linguistic backgrounds for whom validated assessment instruments may be unavailable. This can be achieved through rigorous systematic adaptation procedures for the establishment of comparable language versions of this tool, valuable for various clinical applications. Such endeavours have the potential to provide access to valuable shared datasets for their use across international aphasia trials, and for comparable clinical work within the aphasiology community.
Keywords: best practicerecommendations; psycholinguistic variables; Aphasia assessment; linguistic and culturaladaptations; comprehensive aphasia test; validation challenges